Axiology of Law and Human Rights: A Few Theoretical Remarks in the Perspective of Internal Integration of Legal Sciences - Bartosz Liżewski (Studia Iuridica Lublinensia, 2023)
The aim of the article is to link two research problems. The first of them concerns the determination of the relationship between the axiology of law and human rights. The task of the second is a presentation of this relationship from the perspective of the internal integration of legal sciences. The article explains the mutual relations between the axiology of law and human rights. The following theses are proposed. The first is that human rights, due to their axiological character, are an integral part of the axiology of the entire legal system. At the level of the Constitution of the Republic of Poland, these are included in the rules of the state system. In essence, they contribute to building an integrated value system. The second thesis materializes in the statement that human rights integrate not only the branches of law, but also legal sciences. They are present in every branch of law, i.e. in constitutional, criminal and civil law, labour law, legal theory and international law. They become the subject of scientific reflection in various legal sciences. For these reasons, human rights perform very important functions in the internal integration of legal sciences. The third thesis concerns the level of international law. Human rights, through the European protection system, integrate the European legal space. The protection standards of the European Court of Human Rights play the main role. They contribute to building a common European axiological dimension of human rights.